Teachers’ Challenges in Teaching English for Young Learners during Indonesia’s School-Based Curriculum - Ridhwan, M.; Yeni, Melda; Husna, Ana Imroatul (Asatiza: Jurnal Pendidikan, 2022)
The goal of this study is to discover the challenges that teachers suffered from when teaching English to young learners in Tembilahan Elementary Schools during the School Based Curriculum in 2018. The quantitative descriptive design was used for this study. Researchers employed questionnaires and interviews as research tools to collect study results, the questionnaire functioning as the primary instrument. Questionnaires and interviews were distributed to ten teachers from nine different primary schools. The findings of the Likert questionnaire data analysis and interviews showed that the most difficult challenges for teachers in teaching English to young learners was learners’ motivation. They all believe that raising motivation was tough, and that was one of the difficulties in teaching English to young learners. The findings of the highest score in the data was the thirteenth statement (motivation), where the total score was 40, and it was a teaches’ challenges in teaching English to young learners in primary schools in Tembilahan.